Super-Inertial Interest Rate Rules Are Not Solutions of Ramsey Optimal Policy. - Jean-Bernard Chatelain; Kirsten Ralf (Revue d'économie politique, 2023)
This paper demonstrates that the equilibrium determined by the commitment of a Central Bank to a non-stationary ("super-inertial") interest rate rule (where the sum of the parameters of the lags of the interest rate exceeds one and does not depend on the persistence of shocks) does not correspond to the unique bounded solution and the stable equilibrium of Ramsey optimal policy for the new-Keynesian model. It always destabilizes inflation because of the rounding errors and the measurement errors of the parameters of the monetary policy transmission mechanism. By contrast, the commitment of a Central Bank to a stationary interest rate rule rule (where the sum of the parameters of lags of the interest rate is strictly below one and depends on the persistence of shocks) corresponds to the unique bounded solution and the stable equilibrium of Ramsey optimal policy.
Keywords: C61; C62; E43; E44; E47; E52; E58; 330; Ramsey optimal policy; new-Keynesian model; Interest rate smoothing; Super-inertial rule; Stability